A formação contemporânea do docente na educação básica - Coelho, Hamilton Batista (2012)
This paper presents an approach on the formation process of the professional teaching of Basic Education. The Brazilian educational policy has been discussed a lot about the process of teacher training, especially training that addresses the integral formation of future teachers. Thus, allies are considered very important for training, or technological devices, advances in technology, legislation and educational philosophy of education here represented by thinkers such as Tardif, Paulo Freire, Giroux, Gadotti among others. The dialogue made between these three aspects - technological and legal philosophical make a new teacher profile is configured as a teacher who is actually prepared to deal with the innovations and the growth of contemporary society. In this respect the modern world itself is mostly very diverse and challenging and makes this modern teacher is prepared to act within the diversity and globalization. Thus preparing the student for this to be a critical citizen, creative and participative society where they are inserted. However, IESs need to have in their plans to work this new profile of a teacher, they fit the role of leading the best policy for teacher education. Therefore, education will have well trained teachers and that they will seek to keep up with continuing education.